Determining the Dominant Variable in Budgeting on Performance Effectiveness / PT (Persero) Indra Karya All Branches in Indonesia - Andreano, Pillipus Resar (International Journal Labs, 2023)
The purpose of this study was to investigate the effect of service quality and patient trust on patient loyalty mediated by patient satisfaction in patients who hospitalized at “CDE” Hospital, Bogor, West Java. A Google Forms online survey on inpatients at